Association between metabolic syndrome and risk of incident dementia in UK Biobank - Qureshi, Danial; Collister, Jennifer; Allen, Naomi E.; Kuźma, Elżbieta; Littlejohns, Thomas (Alzheimer's & dementia, 2024)
INTRODUCTION The association between metabolic syndrome (MetS) and incident dementia remains inconclusive. METHODS In 176,249 dementia‐free UK Biobank participants aged ≥60 years at baseline, Cox proportional‐hazards models were used to investigate the association between MetS and incident dementia. MetS was defined as the presence of ≥3 of the following: elevated waist circumference, triglycerides, blood pressure, blood glucose, and reduced high‐density lipoprotein cholesterol. RESULTS Over 15 years of follow‐up (median = 12.3), 5255 participants developed dementia. MetS was associated with an increased risk of incident dementia (hazard ratio [HR]: 1.12, 95% confidence interval [CI]: 1.06, 1.18). The association remained consistent when restricting to longer follow‐up intervals: >5 to 10 years (HR: 1.17, 95% CI: 1.07, 1.27) and >10 years (HR: 1.22, 95% CI: 1.12, 1.32). Stronger associations were observed in those with ≥4 MetS components and in apolipoprotein‐E (APOE)‐ε4 non‐carriers. DISCUSSION In this large population‐based prospective cohort, MetS was associated with an increased risk of dementia. Highlights MetS was associated with a 12% increased risk of incident all‐cause dementia. Associations remained similar after restricting the analysis to those with longer follow‐up. The presence of four or five MetS components was significantly associated with dementia. Stronger associations were observed in those with a low genetic risk for dementia.